The Discourse Battle on the Establishment of Confucian State University in The Bangka Belitung Islands Province - Izcha Pricispa; Yang Azzahra; Nandini Putri; Herza Herza (Faculty of Social Science, Universitas Negeri Malang, 2023)
The Province of Bangka Belitung Islands is designated by the central government for theestablishment of the Confucian State University (Perguruan Tinggi Negeri/PTN Konghucu).However, the government's initiative to build this Confucian State University has sparkeddiverse reactions among the residents of Bangka Belitung: some opposing it, some supportingit, and others questioning it. This study analyzed how each party constructs its discourse tosway public opinion. Furthermore, it investigated the social and legal repercussions of thisdiscourse battle, with the intention of providing insights for considerations or recommendationsto relevant stakeholders. This research method is descriptive qualitative, involving primary andsecondary data collection. Primary data was gathered through direct observation, interviews,and Focus Group Discussions (FGD). Meanwhile, secondary data was sourced from onlinenews, books, journals, and previous research findings. Through this study, researchers identifythe varying discourses presented by each party, reflecting both favorable and unfavorableperspectives.